Majority voting leads to unanimity - Geir B. Asheim; Carl Andreas Claussen; Tore Nilssen (University of Oslo, Department of Economics, 2005)
We consider a situation where society decides, through majority voting in a secret ballot, between the alternatives of `reform' and `status quo'. Reform is assumed to create a minority of winners, while being efficient in the Kaldor-Hicks sense. We explore the consequences of allowing binding transfers between voters conditional on the chosen alternative. In particular, we establish conditions under which the winners wish to compensate all losers, thus leading to unanimity for reform, rather than compensating some losers to form a non-maximal majority. The analysis employs concepts from cooperative game theory.
Keywords: C71; D72; 330; voting; reform; status quo; Kaldor-Hicks sense; chosen alternative; unanimity for reform; cooperative game theory; Wahlsystem; Kooperatives Spiel; Kaldor-Hicks Kriterium